Avaliação dos resultados da produção hospitalar do Hospital Universitário de Santa Maria (HUSM) a partir do processo de contratualização - Pinto, Giovana Petry (2024)
Hospital contracting with the Unified Health System is a complex process that requires collaboration between hospitals and public health managers, establishing goals, responsibilities and remuneration criteria to ensure the efficiency of resources and the quality of care for the population. Based on this context, the study aims to analyze the contracting of the University Hospital of Santa Maria (HUSM) in relation to the performance of hospital production, in the period from 2019 to 2022. In methodological terms, the execution of the contract and the billing of hospital production were compared with the agreed goals and simulations of two financial scenarios with projections until 2030, using the inventory and flow model. In terms of results, the evaluation of the financial reports revealed discrepancies between the quantities contracted and those actually realized. In the first, Medium and High Complexity (MAC) funding was identified as the main support due to the aging population and the increase in complex treatments, while the Strategic Actions and Compensation Fund (FAEC) would have a more specific function, being used for emergencies. And in the second, which combined financing, it was concluded that HUSM will need to expand the infrastructure to high complexity and optimize medium complexity to ensure the sustainability of services by 2030. Based on this, the proposal for contracting for the HUSM focused on continuous improvement and feasible goals that meet hospital conditions and the local SUS manager, considering population growth and aging and births aligned with the hospital morbidity of the elderly population from 2023 to 2030. The projections reveal a mismatch between the volume and resources allocated to medium and high complexity, with medium complexity absorbing 75% of the procedures and 48% of the resources, while high complexity concentrates 52% of the resources in 25% of the procedures. These mismatches indicate the need for institutional policies that promote a balance between goals, resources, training, teaching, research and service to the population. These results may support managers in the contracting process, ensuring the efficiency of financial and operational resources and preserving the quality of services. This managerial approach also enables managers to continuously monitor and adapt performance, contributing to efficiency in health services.